(untitled) (Medico Legal Update, 2021)
Background: Cervical polyps are the commonest cervicallesions, affecting up to 10% of women, with a reported recurrence rate of 6.2%, they arise from the endocervical canal or, less frequently, from the ectocervix, and vary in size from 5 mm to 50 mm. Symptomatic polyps are significantly more frequent in the premenopausal women, while asymptomatic polyps are significantly more common in post-menopausal women. Aim of the Study: Screening for cervical polyps among women attending Salah-Aldin general hospital. Patients and Method: A cross sectional study conducted in outpatients clinic and obstetrical ward in Salah El-Din general hospital at the period from the 1st of March 2018 to the end of August 2018. Simple random sample of (200) women in different ages were included. Results: 200 women were enrolled in this study with the mean age of them were (27.30±6.8 years),the BMI mean of the patients with polyp was (30.2±2.1),4(40%) in age group between 26-35years. Patients with polyps have ? 1 parity 9(9%) and 1(10%) in nulliparous. Conclusion: The frequency of cervical polyp was 5% with no relation to the age, and 60% of the patients were healed.